Pest categorisation of Puccinia pittieriana. (24th November 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of Puccinia pittieriana, the causal agent of common rust of potato, for the EU. The pathogen is a single taxonomic entity and reliable methods exist for its detection and identification. Cultivated potato ( Solanum tuberosum ) and tomato ( Solanum lycopersicum ) are the main hosts of P. pittieriana . Some wild solanaceous plants can also be affected by the pathogen. P. pittieriana is present in countries of South and Central America (most commonly at elevations of 3, 000–4, 000 m), but uncertainty exists about its presence in Bolivia and Paraguay. The pathogen is not known to occur in the EU and is listed in Annex IIAI of Directive 2000/29/EC. P. pittieriana could potentially enter the EU mainly on living host plants and infested soil attached to potato tubers originated in infested areas. Potato and tomato crops are widely distributed in the EU and the prevailing climatic conditions, at least in part of the risk assessment area, are suitable for the establishment and spread of the pathogen. There is uncertainty on the yield/quality losses currently caused by the pathogen in the infested areas. Nevertheless, it is expected that the introduction and spread of P. pittieriana in the EU could impact potato and tomato production, although the magnitude is unknown. Cultural practices and chemical measures may reduce the inoculum sources but they cannot eliminate the pathogen. Phytosanitary measures are available to mitigate the risk of introduction and spread of the pathogen in the EU. P. pittieriana meets all the criteria assessed by EFSA for consideration as a potential Union quarantine pest. As P. pittieriana is not known to occur in the EU, this criterion assessed by EFSA to consider it as a Union regulated non‐quarantine pest is not met.